INFLUENCE OF SILICA COLLOID ON RHEOLOGY OF CEMENT PASTE WITH SUPERPLASTICIZER - T.H. Chuong; P.V. Nga (Universitas Gadjah Mada, 2008)
Information of rheological behavior of binder paste is important for proportioning high slump concrete mixture at low water to cement ratios. This paper presents experimental data on the rheological property of silica colloid incorporated binder paste using naphthalene based and polycarboxylate based superplasticizer, compared to that of silica fume incorporated binder paste. Experimental data showed that silica colloid incorporated binder is compatible to tested superplasticizers in the all investigated range of silica colloid content, whereas the pastes incorporated with high silica fume content (over 10%) indicated incompatibility, especially to naphthalene based superplasticizer. There was also found out saturated content of superplasticizer corresponding to every kind of binder and water-binder ratio, with and without set retarding admixture.